1983
DOI: 10.1111/j.1464-410x.1983.tb07081.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Concentration of Lignocaine after Application of 2% Lignocaine Gel in the Urethra

Abstract: In 35 patients undergoing topical anaesthesia with lignocaine (lidocaine) gel (2% Xylocaine gel) the concentration of lignocaine base was measured in repeated venous blood samples. Twenty patients (group I) were given 20 ml of 2% lignocaine gel (400 mg lignocaine) and 5 patients (group II) received 40 ml (800 mg lignocaine) endourethrally. These 2 groups of patients underwent either dilation of the urethra or urethrocystoscopy. Ten patients (group III) undergoing transurethral resection of the prostate or a bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…7 However, topical lidocaine is absorbed slowly and incompletely. 7 Previous reports 8,9 suggest that lidocaine is maximally absorbed at 15-60 minutes. In the present study, lidocaine gel was maintained in the urethra for a minimum of 15 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, topical lidocaine is absorbed slowly and incompletely. 7 Previous reports 8,9 suggest that lidocaine is maximally absorbed at 15-60 minutes. In the present study, lidocaine gel was maintained in the urethra for a minimum of 15 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…The diverse efficacy of lidocaine gel may be because the absorption of topical lidocaine is slow and incomplete. Several groups have demonstrated that maximal lidocaine absorption requires 15 to 60 minutes [5, 12]. …”
Section: Discussionmentioning
confidence: 99%
“…Whilst reflecting current clinical practice, the volume and amount of lignocaine gel used in the present study (10 ml of 2% gel= 200 mg lignocaine) is below that recommended by some manufacturers. There can be no doubt that increasing the quantity of lignocaine instilled would increase drug uptake from the urethra [16]. The clinical efficacy of such a strategem has been examined in detail by Brekkan et d. [lo].…”
Section: Discussionmentioning
confidence: 99%